Drama-Based Instruction: Its Effect on the Reading Skills of Grade 7 Learners - Ruchel B. Alpasan; Ma. Fe B. Belasoto (Researchparks Publishing, 2022)
This mixed method research was conducted to determine if drama-based instruction is an effective strategy to improve the reading skills of Grade 7 learners in their remedial classes. There were 100 randomly selected participants of the study, of which 50 were assigned to the experimental group and 50 to the control group. Through a self-made instrument which had undergone validation from a panel of experts and reliability testing, the data were gathered. The findings revealed that the level of reading skills of Grade 7 learners before and after exposure to drama-based instruction and traditional remedial reading teaching was average. However, t-test for independent samples revealed a significant difference in the pre-test and posttest performance of both drama-based instruction and traditional remedial reading teaching. There was no significant difference in the pretest between the experimental and the control group and there was also no significant difference in the post test between the two groups. There were learners who enjoyed and developed teamwork in drama-based instruction, but there were also learners who remained shy and refused to cooperate. It can be said that both the drama-based instruction and traditional remedial reading teaching were effective in helping to improve the reading skills of the learners.